Media coverage of contaminants in pilot whales in the Faroe Islands - Elsa F. Helmsdal; Amanda D. Boyd; Jesper Bo Nielsen; Maria Skaalum Petersen (International Journal of Circumpolar Health)
This study examines the portrayal of contaminants in pilot whale in Faroese media from 1977 to 2022. Pilot whale is integral to Faroese culture but has come under scrutiny due to health concerns linked to contaminants. Given the role of media in shaping public understanding of health risks, our research assesses how four main Faroese media outlets have presented the issue to the public. We analysed 227 newspaper articles, radio, and television news stories, focusing on contaminants, mentioning of scientific studies or researchers, the demographic groups identified as at risk, and mentions of government advisories on whale meat consumption. Our findings indicate a predominant portrayal of contaminants as harmful, with a substantial emphasis on the risks to developing foetuses and children. Scientific studies, particularly those led by the Department of Occupational Medicine and Public Health in the Faroe Islands, were frequently cited. Despite varying advisories over the years, the narrative consistently highlighted the health risks associated with pilot whale consumption. This study contributes to broader discussions on environmental health communication by illustrating how localised media coverage can shape public risk perception, offering insights relevant to communities facing similar dilemmas between traditional hunting and public health.